Case report: Gene mutations and clinical characteristics of four patients with osteopetrosis - Chen, Yu; Zhou, Lina; Guan, Xianmin; Wen, Xianhao; Yu, Jie; Dou, Ying (Frontiers in Pediatrics, 2023)
Osteopetrosis is characterized by increased bone density caused by decreased osteoclasts or dysfunction of their differentiation and absorption properties, usually caused by biallelic variants of the TCIRG1 and CLCN7 genes. Herein, the clinical, biochemical, and radiological manifestations of osteopetrosis in four Chinese children are described. Whole‐exome sequencing identified compound heterozygous variants of the CLCN7 and TCIRG1 genes in these patients. In Patient 1, two novel variants were identified in CLCN7: ene:c.880T>G(p.F294V) and c.686C>G(p.S229X). Patient 2 harbored previously reported pathogenic variant c.643G>A(p.G215R) in CLCN7. Patient 3 had a novel variant c.569A>G(p.N190S) and a novel frameshift variant c.1113dupG(p.N372fs) in CLCN7. Patient 4 had a frameshift variant c.43delA(p.K15Fs) and variant c.C1360T in TCIRG1, resulting in the formation of a premature termination codon (p.R454X), both of which were reported previously. Our results expand the spectrum of identified genetic variation in osteopetrosis and provide a deeper understanding of the relations between genotype and clinical characteristics of this disorder.